Efektivitas Manajemen Pembiayaan Ijarah Multijasa pada Layanan Pembiayaan FIF Group - Andi Lisa Aryani Hamjan; Hasanah; Muhammad Fakhri Amir (Journal of Islamic Economic Studies, 2025)
Ijarah Multijasa financing has become one of the essential instruments in the development of Islamic financial services in Indonesia, particularly in supporting the financing needs of pilgrimage activities such as Hajj and Umrah. However, the effectiveness of financing management within non-bank institutions such as FIF Group has received limited scholarly attention. This study aims to analyze the effectiveness of Ijarah Multijasa financing management for Hajj and Umrah advance funds provided through the Amitra unit of FIF Group. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation, involving Amitra employees and customers as key informants. The findings indicate that the financing implementation adheres to sharia principles, as shown by the proper analysis of customer eligibility, the absence of late payment penalties, the non-imposition of early settlement penalties, and the transparent explanation of the contract prior to signing. The reminder system implemented by Amitra also contributes to timely installment payments. Nonetheless, customer understanding of sharia contractual concepts still requires improvement. This study offers theoretical implications concerning the importance of sharia compliance in financing management and practical recommendations to strengthen customer education and communication for enhancing the quality of Islamic financing services.